2019
DOI: 10.1002/ijc.32047
|View full text |Cite
|
Sign up to set email alerts
|

Mediation of associations between adiposity and colorectal cancer risk by inflammatory and metabolic biomarkers

Abstract: Inflammation and hyperinsulinemia may drive associations between adiposity and colorectal cancer (CRC) risk, but few studies have examined this hypothesis using mediation analysis. We used inverse odds ratio weighting and logistic regression to calculate odds ratios (OR) and 95% confidence intervals (CI) for estimated total effects (ORTE) of body mass index, waist circumference, and adult weight gain on CRC risk, and estimated effects operating through seven inflammatory and metabolic biomarkers (natural indir… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 58 publications
(116 reference statements)
0
3
0
Order By: Relevance
“…95%CI, 1.14-1.73) was explained by all inflammatory (CRP, interleukin-6, tumour necrosis factor receptor 2, and macrophage inhibitory cytokine-1) and metabolic (adiponectin, C-peptide, and soluble leptin receptor (sOB-R)) biomarkers (OR NIE 1.26; 95%CI, 0.97-1.52) 38 . The authors repeated the mediation analysis separately for the two biomarker groups, assuming that the pathways were independent.…”
Section: Discussionmentioning
confidence: 98%
“…95%CI, 1.14-1.73) was explained by all inflammatory (CRP, interleukin-6, tumour necrosis factor receptor 2, and macrophage inhibitory cytokine-1) and metabolic (adiponectin, C-peptide, and soluble leptin receptor (sOB-R)) biomarkers (OR NIE 1.26; 95%CI, 0.97-1.52) 38 . The authors repeated the mediation analysis separately for the two biomarker groups, assuming that the pathways were independent.…”
Section: Discussionmentioning
confidence: 98%
“…for metabolic biomarkers such as adiponectin, C-peptide, and soluble leptin receptors. 41 Interestingly, leptin and soluble leptin receptors may have been mediators in all three previous studies. These findings are partially consistent with our current findings, even though we were unable to compare our results with those from previous studies due to differences in the number In this study, we used a relatively new approach within the causal mediation analysis framework to estimate certain path-specific effects identified from the observed data.…”
Section: Discussionmentioning
confidence: 76%
“…Few studies have formally examined the mechanistic associations between obesity and CRC risk using mediation analysis. [38][39][40][41] Ho et al reported that leptin and insulin partially explained the association between waist circumference and the risk of CRC in a Women's…”
Section: Discussionmentioning
confidence: 99%
“…High fasting insulin concentrations are associated with increased risks of breast 107,108 , endometrial 102 , pancreatic 109,110 , colorectal 111 , renal 112 , gastric 113,113 and liver cancers 114,115 . In an MR mediation analysis, high fasting insulin mediated 19% (95% CI: 5-34%) of the association of obesity with endometrial cancer 102 , and observational studies have reported that high insulin may also largely mediate associations between BMI and colorectal cancer 116,117 .…”
Section: Hyperinsulinemiamentioning
confidence: 98%